2022
DOI: 10.1186/s12885-022-09796-7
|View full text |Cite
|
Sign up to set email alerts
|

A tool for predicting overall survival in patients with Ewing sarcoma: a multicenter retrospective study

Abstract: Objective The aim of this study was to establish and validate a clinical prediction model for assessing the risk of metastasis and patient survival in Ewing's sarcoma (ES). Methods Patients diagnosed with ES from the Surveillance, Epidemiology and End Results (SEER) database for the period 2010-2016 were extracted, and the data after exclusion of vacant terms was used as the training set (n=767). Prediction models predicting patients' overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The predictive accuracy may be improved by a nomogram including size, location of osteonecrosis and GPx4 levels in future study. [25,26] Finally, ROC curve analysis was performed to test the efficacy of serum GPx4 in the diagnosis and progression prediction of NONFH. The AUC of ROC was 0.808 for serum GPx4 in the diagnosis of NONFH and 0.847 in the prediction of collapse of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive accuracy may be improved by a nomogram including size, location of osteonecrosis and GPx4 levels in future study. [25,26] Finally, ROC curve analysis was performed to test the efficacy of serum GPx4 in the diagnosis and progression prediction of NONFH. The AUC of ROC was 0.808 for serum GPx4 in the diagnosis of NONFH and 0.847 in the prediction of collapse of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell sequencing analysis was performed to find differential glutamine metabolism-related genes among individual BC cells. Using the Cox risk model and LASSO regression, new risk profiles were constructed based on the expression levels of genes related to glutamine metabolism in the TCGA-BC dataset (24). In addition, in breast cancer, glutamine metabolic profiles can be used to identify changes in immune infiltration and immune checkpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Ewing sarcoma (ES) is the second-most common primary bone tumor that is highly malignant and has a peak incidence in the second decade of life [ 1 ]. It affects 2.6 and 2.8 children per million in the United States and Germany, respectively [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…ES typically develops in the femur, shoulder blades, ribs, and pelvic area [ 3 ]. Previous research has found that tumors most commonly arise in the tubular bones of the extremities (46%), mostly in the lower extremities, followed by the pelvis (25%), trunk comprising ribs and spinal trunk (22%), and other locations (6%) [ 1 ]. The 5-year overall survival (OS) rate for patients with localized ES has grown to 65%, due to the use of surgery, chemotherapy, and radiation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%